Urgensi Pelaporan Keuangan Untuk Peningkatan Usaha Mikro Kecil Menengah (UMKM) Dalam Rangka Pengembangan Bisnis - Sulastiningsih, Sulastiningsih; Beta Asteria; Ary Sutrichastini (JCSE: Journal of Community Service and Empowerment, 2025)
The purpose of this Community Service (PkM) is to provide knowledge, insight and skills regarding financial reporting for business development to 31 MSME actors in Dukuh Ngampo, Pacarejo Village, Semanu District, Gunung Kidul Regency, Special Region of Yogyakarta Province, through training and mentoring activities. Training materials include the urgency of financial reporting, the process of preparing financial reports, financial performance analysis, financial management planning and control. The training methods used are lectures, discussions, questions and answers and case analysis. After this PkM activity was carried out, there was an increase in literacy, knowledge, insight and skills of 31 MSME actors in Dukuh Ngampo regarding the urgency of financial reporting and financial reports as a basis for planning, controlling and making economic decisions for MSME business development.